Penerapan Metode Tilawati Untuk Meningkatkan Kemampuan Membaca Al-Quran Siswa Pada Mata Pelajaran THQ - Latipah, Aila; Masripah, Masripah; Komariah, Iis (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
By examining the tilawati approach helps fifth graders become better Qur'an readers as the meaning of this research. Utilizing a pre- and post-test methodology, this study employs a quasi-experimental approach in MIN 2 Garut's fifth grade. Interviews, observations, tests, also documentation actualized for gathering data. Data analysis procedures such as normality testing, homogeneity tests, hypothesis tests, and N Gain tests were used. The research found that students' Qur'an reading skills, particularly their ability to read juz amma, were significantly improved when the tilawati technique was used. Results from the Ngain Score calculation test indicated that the experimental class that got the tilawati method learning treatment had an average Ngain score of 62.3724, or 62%, indicating that it was quite successful in develop students skill to receits Qur'an. Treatment group achieved an average N Gain score of 6.091, which was considered successful when rounded to 6%. In contrast, the control group did not get any therapy. Thus, it is evident that the experimental group that received tilawati-based instruction significantly outperformed the control group in enhancing students' Qur'an reading skills.